Risk sharing and the systemic fragilities of debt-economy - Mirakhor, Abbas (Intellectual Discourse, 2018)
This study explains risk transfer, associated with debt-based financing, as the main cause of financial crises in the world. It presents the case for a financial architecture based on risk sharing that, in turn, is likely to make the financial system less fragile and more stable. This study also highlights the significance of Islamic finance in this regard.